Lelang Barang Jaminan pada Perum Pegadaian Syariah Perspektif Fatwa Dsn Mui Nomor 25 Tahun 2002 (Studi Kasus di Sibuhuan Kecamatan Barumun Kabupaten Padang Lawas) - Pohan, Irma Yanti; Zahra, Fatimah (Universitas Ekasakti, 2023)
The sharia pawnshop in Sibuhuan, Barumun District, Padang Lawas Regency is a non-bank institution that also helps people from the micro class by providing financial assistance by pawning goods as collateral, in order to get a sum of money worth the goods guaranteed by agreement between the customer and the pawnshop institution. However, if it is due and the customer has not paid off the collateral, the pawnshop contacts the customer to ask whether the customer still wants to extend the collateral or not, and if the collateral is still being extended. then the customer must pay a fine for extending the collateral. And if the customer does not redeem the collateral, the pawnshop may auction the collateral. This research uses empirical or field legal research by means of interviews, questionnaires or questionnaires and observations. Meanwhile, in collecting data, researchers used primary, secondary data and relevant journals. The result of this research is that the customer needs knowledge regarding collateral items auctioned by the Pegadaian institution in accordance with the auction procedures carried out. For this reason, pawnshop institutions must explain to customers that the process of buying and selling pawned goods or auctioned goods must have an element of willingness in buying and selling auctioned goods, because the buying and selling of auctioned goods is legal and good according to the regulations in the DSN-MUI Fatwa. And the proceeds from the sale are not enough to pay off the Rahn's debt, so the Rahn is not obliged to pay the shortfall.